Help STPM, SPM students choose right career path - Leow, Serena Wai Yee *; Leow, Kenneth (New Straits Times Press (M) Bhd., 2023)
Letters: We must support and encourage Sijil Pelajaran Malaysia and Sijil Tinggi Persekolahan Malaysia students to pursue higher education.